Dye-sensitized Solar Cell Based on Composite Poly(ethylene oxide) Electrolyte with Natural Carmine Pigment - Surassawatee Jamikorn (Science Faculty of Chiang Mai University, 2019)
Carmine particles which were prepared by precipitating natural cochineal extract with tin ions were incorporated into a solid-state composite poly(ethylene oxide) electrolyte (CPE). The conductivity of the modified CPE as calculated from the electrochemical impedance spectra, was increased with increasing amount of carmine varied from 10%w/w to 48%w/w. This modified CPE was used as solid electrolyte to fabricate DSSCs and was found to enhance the performance of DSSC using carminic acid and cochineal extract as sensitizers. The overall energy conversion efficiency of DSSCs increased from 0.11% to 0.93% and from 0.28% to 0.73% for carminic acid and cochineal extract sensitizers, respectively. The crystallinity and morphology of the CPEs were further examined by X-ray diffraction and scanning electron microscopy.